Development of Guar Gum Hydrogel Containing Sesamol-Loaded Nanocapsules Designed for Irritant Contact Dermatitis Treatment Induced by Croton Oil Application - Vinicius Costa Prado; Kauani Moenke; Bárbara Felin Osmari; Natháli Schopf Pegoraro; Sara Marchesan Oliveira; Letícia Cruz (MDPI AG, 2023)
Irritant contact dermatitis is usually treated with corticosteroids, which cause expressive adverse effects. Sesamol is a phenolic compound with anti-inflammatory and antioxidant properties. This study was designed to evaluate a hydrogel containing sesamol-loaded ethylcellulose nanocapsules for the treatment of irritant contact dermatitis. The nanocapsules presented a size in the nanometric range, a negative zeta potential, a sesamol content close to the theoretical value (1 mg/mL), and a 65% encapsulation efficiency. Nanoencapsulation protected sesamol against UVC-induced degradation and increased the scavenging activity assessed by ABTS and DPPH radicals. The hydrogels were prepared by thickening the nanocapsule suspensions with guar gum (2.5%). The hydrogels maintained the nanometric size of the nanocapsules and a sesamol content of approximately 1 mg/g. The HET-CAM assay classified the hydrogels as nonirritating. The in vitro release of the hydrogel containing sesamol in the nanoencapsulated form demonstrated an initial burst effect followed by a prolonged sesamol release and a lower skin permeation in comparison with the hydrogel containing free sesamol. In addition, it exhibited the best anti-inflammatory effect in the irritant contact dermatitis model induced by croton oil, reducing ear edema and inflammatory cells infiltration, similar to dexamethasone (positive control). Therefore, the hydrogel containing sesamol in the nanoencapsulated form seemed to have a therapeutic potential in treating irritant contact dermatitis.